DISCRIMINANT FUNCTIONS AND THEIR MISCLASSIFICATION ERRORS - I W. MANGKU (Dept. of Mathematics, IPB University, 2002)
This paper is a survey study on discriminant functions and their misclassiﬁcation errors. Here we consider three groups of discriminant functions, namely discriminant functions for respec- tively multivariate normal variables, multivariate binary variables, and a mixture of multivariate binary and normal variables. Finally we derive their misclassiﬁcation errors.